Manufacturing method of electrode material
The method of spray drying a lithium vanadium oxide and carbon composite in a water-based solution reduces manufacturing time, addressing the inefficiencies of existing methods and enabling the production of high-rate electrode materials quickly.
Patent Information
- Application Number
- JP2023170435
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
AI Technical Summary
The existing methods for manufacturing a composite of lithium vanadium oxide and carbon are time-consuming, requiring at least 60 hours, which hinders the production of small lots of large variety and is not suitable for quick production demands.
A method involving the preparation of a mixture with a vanadium source, lithium source, and carbon in a water-based solution, adjusting the pH to 5 or higher, and then spray drying the solution to vaporize the liquid, resulting in the crystallization of lithium vanadium oxide, cationic disordering, and the combination with carbon in a single step, significantly reducing the manufacturing time.
This method enables the production of an electrode material with good rate characteristics in a short time, enhancing the efficiency and capability to meet quick production demands.
Smart Images

Figure 2025059983000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a composite of lithium vanadium oxide and carbon, which can be used as an electrode material for secondary batteries and capacitors. [Background technology]
[0002] Lithium vanadium oxide, represented by lithium vanadate with the chemical formula Li3VO4, is used as an electrode material for secondary batteries and capacitors. This lithium vanadium oxide is also known as lithium titanate (Li4Ti5O 12 ) and B-type titanium oxide (TiO2(B)). Moreover, lithium vanadium oxide has a higher charge / discharge potential (V vs Li / Li+) than graphite. Therefore, a power storage device using lithium vanadium oxide as the negative electrode material is expected to have a high energy density and a high level of safety.
[0003] It has also been reported that the theoretical capacity of a capacitor using lithium vanadium oxide as the negative electrode material is more than twice as high as that of lithium titanate. In terms of cycle characteristics, capacitors using lithium vanadium oxide as the negative electrode material maintain a high capacity retention rate and high charge / discharge efficiency.
[0004] Therefore, this lithium vanadium oxide is being researched for use in various types of power storage devices. Examples of power storage devices include lithium ion secondary batteries using metal compound particles for the positive and negative electrodes, and hybrid capacitors using activated carbon for the positive electrode and a material capable of reversibly adsorbing / desorbing lithium ions for the negative electrode. In order to increase the electrical conductivity of the electrode, highly electrically conductive carbon is added as a conductive assistant to the electrode material containing lithium vanadium oxide as the electrode active material. The rate characteristics of the electrode material, i.e., the charge / discharge capacity at high rates, are improved by compounding the carbon, which is a conductive assistant, with lithium vanadium oxide.
[0005] The following method is generally known as a method for producing lithium vanadium oxide: A lithium source and a vanadium source are mixed together by a solid-phase method or a liquid-phase method, and then calcined at 600° C. or higher to cause crystallization and crystal growth (see, for example, Non-Patent Document 1).
[0006] However, lithium vanadium oxide crystals usually have a β-phase crystal structure. The β-phase crystal structure is a wurtzite type, and the space group is Pmn21. An energy storage device using a lithium vanadium oxide crystal having a β-phase crystal structure as an electrode material has a problem with rate characteristics. Specifically, when the C rate is increased, the input and output characteristics are rapidly deteriorated. Alternatively, when the charge and discharge density is increased, the charge capacity that can be charged and the discharge capacity that can be discharged are reduced.
[0007] Therefore, a method has been proposed in which the structure of lithium vanadium oxide crystals is transformed from the β phase to the γ phase by firing at 770°C or higher (see, for example, Non-Patent Document 2). The crystal structure of the γ phase is a so-called LISICON (Lithium Super Ionic Conductor) type, and is a Pnma crystal structure. Lithium vanadium oxide crystals having a γ phase crystal structure have a tetrahedral LiO4 coordination structure and a tetrahedral VO4 coordination structure as their basic skeletons, and an octahedral LiO6 coordination structure.
[0008] Furthermore, in order to change the lithium vanadium oxide crystals into a cation-disordered structure, mechanical milling can be carried out after firing (see, for example, Patent Document 1). In the mechanical milling, mechanical energy is applied using, for example, a planetary ball mill, a ball mill, a bead mill, a rotary mill, a vibration mill, or the like.
[0009] The cation disordered structure is a structure in which cations are disordered. In this cation disordered structure, all or part of the various long-range orders that appear in the range of angles lower than the peak of the incident angle 2θ of about 32.2 degrees analyzed by powder X-ray analysis are broken and become random. In other words, in the cation disordered structure, the regularity of the arrangement of the VO4 coordination structure and the LiO4 coordination structure at the distance that appears in the range of angles lower than the peak of about 32.2 degrees is lost.
[0010] After the lithium vanadium oxide is produced, the lithium vanadium oxide is mixed with carbon to form a composite of the lithium vanadium oxide and the carbon. In the composite process, a mechanical milling method is used. In the mechanical milling method, mechanical energy is applied using, for example, a planetary ball mill, a ball mill, a bead mill, a rotary mill, a vibration mill, or the like. [Prior art documents] [Non-patent literature]
[0011] [Non-Patent Document 1] Zhiyong Liang, et al., Journal of Power Sources, 2014, Volume 252, Pages 244-247.https: / / doi.org / 10.1016 / j.jpowsour.2013.12.019 [Non-Patent Document 2] Chaoyi Liao, et al., ADVANCED ENERGY MATERIALS, 2018, Vol.8, Issue.9, 1701621.https: / / doi.org / 10.1002 / aenm.201701621 [Patent documents]
[0012] [Patent Document 1] Patent No. 7208147 Summary of the Invention [Problem to be solved by the invention]
[0013] In such a method for producing a lithium vanadium oxide / carbon composite, the firing step requires at least 12 hours, the cation disordering step requires at least 36 hours, and the composite mechanical milling step requires at least 12 hours, i.e., it takes at least 60 hours to produce a lithium vanadium oxide / carbon composite.
[0014] In recent years, customer needs for small-lot, high-mix production have been on the rise. To minimize inventory and enable rapid production of orders, it is necessary to shorten the time required for the production of electronic components.
[0015] An object of the present invention is to provide a method for producing an electrode material, which is a composite of lithium vanadium oxide and carbon, in a short period of time. [Means for solving the problem]
[0016] In order to achieve the above object, the method for producing an electrode material of the present embodiment is a method for producing an electrode material that is a composite of lithium vanadium oxide and carbon, and includes the steps of: preparing water or a mixed solution containing water; preparing a raw material solution of the composite by adding a vanadium source, a lithium source, and the carbon to the water or the mixed solution containing water; adjusting the pH of the raw material solution to pH 5 or higher; and spray-drying the raw material solution by spraying the raw material solution and exposing it to hot air to evaporate the liquid from the raw material solution.
[0017] In the spray drying step, the lithium vanadium oxide may be crystallized to change the lithium vanadium oxide into a cation-disordered structure, and the lithium vanadium oxide and the carbon may be composited.
[0018] The method may include a stirring step of stirring the raw material liquid with a homogenizer before the spray drying step, and a dispersion step of pouring the raw material liquid into a reaction vessel and dispersing the vanadium source, the lithium source, and the carbon in the reaction vessel while rotating before the spray drying step.
[0019] In the preparation step, the carbon may be spherical or have an aspect ratio of 40 or less.
[0020] In the preparation step, carbon black may be added as the carbon.
[0021] In the preparation step, Ketjen black may be added as the carbon.
[0022] In the preparation step, the carbon may be added to the composite in an amount of 20 wt % or less.
[0023] In the preparation step, carbon nanotubes may be added as the carbon to the composite body in an amount of 40 wt % or more. Effect of the Invention
[0024] According to the present invention, an electrode material having good rate characteristics can be produced in a short period of time. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a graph showing X-ray diffraction spectra by powder X-ray diffraction analysis of lithium vanadium oxide crystals, in which (a) shows the X-ray diffraction spectrum of a cation-disordered crystal structure, (b) shows the X-ray diffraction spectrum of a lithium vanadium crystal structure with long-range order obtained by this production method, and (c) shows the X-ray diffraction spectrum of a lithium vanadium oxide crystal having a β-phase crystal structure obtained through a firing process. [Diagram 2]2 is a flowchart showing a manufacturing method of the present embodiment. [Diagram 3] 1A and 1B are SEM images of the surface of the composite of lithium vanadium oxide and Ketjen black in Example 2, where (a) is a 13,000x magnification and (b) is a 10,000x magnification. [Figure 4] 1A and 1B are SEM images of a cross section of an electrode using a composite of lithium vanadium oxide and Ketjen black in Example 1, where (a) is a SEM image at a magnification of 2.2,000 times, and (b) is a SEM image at a magnification of 20,000 times. [Diagram 5] 1A and 1B are SEM images of the surface of the composite of lithium vanadium oxide and acetylene black in Example 2, where (a) is a 3,000-fold magnification and (b) is a 9,000-fold magnification. [Figure 6] 13A and 13B are SEM images of a cross section of an electrode using a composite of lithium vanadium oxide and acetylene black in Example 2, where (a) is a SEM image at a magnification of 2.2,000 times, and (b) is a SEM image at a magnification of 20,000 times. [Figure 7] 13 shows SEM images of the composite of the lithium vanadium oxide of Example 3 and 20 wt % multi-walled carbon nanotubes, where (a) is a cross-sectional image at a magnification of 20,000 times, and (b) is a surface image at a magnification of 20,000 times. [Figure 8] 13A and 13B are SEM images of the surface of the composite of lithium vanadium oxide and 40 wt % multi-walled carbon nanotubes in Example 4, where (a) is a 7,000x magnification and (b) is a 30,000x magnification. [Figure 9] 1 shows powder X-ray diffraction spectra, where (a) is for Example 1, (b) is for Example 2, (c) is for Example 3, and (d) is for Example 4. [Figure 10] 1 is a graph showing the relationship between current density and capacity during discharge in Examples 1 to 3 and Comparative Example 1. [Figure 11] 1 is a graph showing the capacity retention rate when discharged at each current density in Examples 1 to 3 and Comparative Example 1. [Figure 12] 1 is a graph showing the relationship between current density and capacity during discharge in Examples 3 and 4 and Comparative Example 1. [Figure 13]1 is a graph showing the capacity retention rate when discharged at each current density in Examples 3 and 4 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the embodiments described below. In the present invention, vaporization refers to a change of a substance from a liquid state to a gaseous state.
[0027] (Industrial Applicability) Lithium vanadium oxide has the chemical formula Li x V y M a O z where x=0.1 to 5, y=0.1 to 5, z=0.1 to 5, a=0 to 2, and M is Mo, W, Si, Cr, or Ti doped into the lithium vanadium oxide crystal, but these do not have to be doped. Typically, lithium vanadium oxide is represented by the chemical formula Li3VO4, and when lithium ions are inserted as an electrode material, it is represented by the composition formula Li 3+b It becomes VO4. b is the inserted lithium ion.
[0028] Lithium vanadium oxide is a material into which lithium ions can be reversibly inserted and removed. Lithium vanadium oxide serves as an electrode material for power storage devices as an electrode active material. To improve electrical conductivity, lithium vanadium oxide is composited with carbon, which is a conductive additive. The composite of lithium vanadium oxide and carbon is particularly suitable for use as an electrode material for power storage devices.
[0029] Examples of the power storage device include a lithium ion secondary battery and a lithium ion hybrid capacitor. In the lithium ion secondary battery, the positive electrode has an active material layer containing a lithium metal compound, the negative electrode has an active material layer containing a lithium vanadium oxide crystal, and the positive electrode and the negative electrode are Faraday reaction electrodes into which lithium ions are reversibly inserted and desorbed. In the lithium ion hybrid capacitor, the positive electrode is a polarizable electrode having, for example, activated carbon, and utilizes the charge storage action of an electric double layer formed at the interface between the activated carbon and the electrolyte, and the negative electrode has an active material layer containing the lithium vanadium oxide crystal, and is a Faraday reaction electrode into which lithium ions are reversibly inserted and desorbed.
[0030] (Method for producing a composite of lithium vanadium oxide and carbon) The method for producing this complex is as follows. First, a vanadium source is dissolved in water with an adjusted pH. The pH of the aqueous solution in which the vanadium source is dissolved may be adjusted. The vanadium source dissolved in water undergoes reversible reactions of ionization, protonation, and deprotonation that occur unevenly depending on the pH, producing VO4 3- The anion containing vanadium is called HVO4. The anion containing VO4 has four oxygen ions bonded to the vanadium atom, and some of the oxygen ions are hydroxylated. For example, this anion is called HVO4. 2- Ion or H2VO4 - ion. Hereafter, VO4 3- The ion and the anion that contains VO4 in their structure are collectively called the VO4 unit.
[0031] A lithium source is also dissolved in the aqueous solution containing the VO4 units. Carbon is also added to the aqueous solution containing the VO4 units. Dissolution of the lithium source, addition of carbon, or both may be performed prior to dissolution of the vanadium source. The lithium source is an ionically dissociable lithium-containing compound that is soluble in water and can also serve as a pH adjuster. The raw material solution to which the lithium source, vanadium source, carbon, and pH adjuster have been added may be stirred until it becomes colorless and transparent using a stirring means such as a magnetic stirrer, an electric motor stirrer, or an air motor stirrer. The change of the raw material solution to colorless and transparent indicates complete dissolution of the lithium source and the vanadium source.
[0032] After preparing the raw material liquid, the water is evaporated from the raw material liquid by a spray drying process. The water is evaporated and concentrated to a saturation concentration or higher. Therefore, in the spray drying process, the VO4 units crystallize while absorbing lithium ions, and lithium vanadium oxide crystals are precipitated, lithium vanadium oxide becomes cationic disordered, and lithium vanadium oxide is further composited with carbon.
[0033] In this way, this composite is produced by simply mixing the lithium source, vanadium source, and carbon in a raw material liquid and subjecting the raw material liquid to a spray-drying process. The spray-drying process takes about 15 minutes. The 15-minute spray-drying process completes the crystallization of lithium vanadium oxide, the cationic disordering of lithium vanadium oxide, and the composite with carbon.
[0034] In the spray drying process, the water is preferably evaporated at a vaporization rate of 1.67 ml / min or more. At a vaporization rate of 1.67 ml / min or more, the aqueous solution in which lithium ions and VO4 units are produced is sprayed into hot air, and the water is instantly evaporated. The water vapor is carried by the hot air and instantly separated from the lithium vanadium oxide crystals. This makes it possible to prevent the lithium vanadium oxide crystals having a cationic disordered crystal structure from contacting water again. This effectively suppresses the recovery of the long-range order of the lithium vanadium oxide crystals.
[0035] The solvent of the raw material liquid is water such as ion-exchanged water or distilled water, or a mixed liquid mainly containing water. In the mixed liquid, water may occupy 50 wt% or more of the solvent. Therefore, an alcohol may be added to the mixed liquid as a solvent to increase the solubility of the lithium source and the vanadium source. As the alcohol, methanol, ethanol, butanol, isopropyl alcohol, etc. are preferably used. When a mixed liquid is used, the liquid component consisting of the solvent mixed with water may be vaporized.
[0036] The vanadium source is a vanadium acetate, sulfate, nitrate, halogen compound, or chelating agent. Specifically, the vanadium source is a metavanadate, vanadium oxide, vanadium(III) acetylacetonate, vanadium(IV) oxyacetylacetonate, vanadium oxytrichloride, vanadium tetrachloride, vanadium trichloride, polyvanadate, or a combination thereof. The metavanadate is, for example, NH4VO3, NaVO3, KVO3, etc. The vanadium oxide is, for example, V2O5, V2O4, V2O3, V3O4, etc.
[0037] The aqueous solution in which the vanadium source is dissolved is adjusted to at least pH 5 or more. Preferably, the aqueous solution in which the vanadium source is dissolved is adjusted to pH 10 or more. When the aqueous solution has a pH of 5 or more, the proportion of VO4 units in the vanadium oxide ions generated in the aqueous phase increases. When the aqueous solution has a pH of 10 or more, HVO4 2- Decreased VO4 3- On the other hand, if the pH of the aqueous solution containing the vanadium source is less than 5, no VO4 units are produced.
[0038] In the spray-drying process, the VO4 unit starts to form a hexagonal close-packed structure by coordinating with other VO4 units from a tetrahedral coordination structure with vanadium ions at the center, and crystal nuclei begin to form in a hexagonal close-packed structure. As the crystal nuclei form as VO5 coordination structures, a hexagonal LiO5 coordination structure is formed while lithium ions are incorporated into some of the gaps formed by the VO5 units. It is presumed that the rapid precipitation results in the formation of lithium vanadium oxide crystals with a hexagonal close-packed structure in which atoms are closely packed, while the coordination structure changes to a hexahedral structure. It is also presumed that this rapid precipitation causes the extremely small crystals that incorporate lithium ions to grow as primary particles while irregularly incorporating lithium ions.
[0039] Therefore, it is believed that there are some parts where the arrangement of hexahedral VO5 and the arrangement of hexahedral LiO5 are irregularly connected. It is believed that this irregular connection causes the arrangement of lithium ions to become disordered, resulting in cation disorder.
[0040] Lithium sources include lithium hydroxide, lithium hydroxide hydrate, lithium acetate, lithium nitrate, lithium carbonate, lithium chloride, and lithium lactate. The vanadium source and lithium source are added to the aqueous phase according to the stoichiometric ratio of lithium vanadium oxide. In the case of Li3VO4, the vanadium source and lithium source are added so that the molar amount of lithium is three times that of vanadium. When lithium hydroxide and vanadium pentoxide are added, the ratio is 1 mole of vanadium pentoxide to 6 moles of lithium hydroxide.
[0041] The lithium source is preferably lithium hydroxide or lithium hydroxide hydrate. Lithium hydroxide or lithium hydroxide hydrate is a strong base, and it is easy to adjust the pH of the aqueous solution in which the vanadium source is dissolved. That is, impurities other than the material source of lithium vanadium oxide are not contained in the aqueous solution. However, other pH adjusters can be used without any particular limitation as long as they are poorly reactive with the lithium source or vanadium compound. Other pH adjusters include hydroxides such as citric acid, ammonia, dimethylamine, trimethylamine, and sodium hydroxide, and the pH can also be adjusted by the concentration of these.
[0042] Carbon can be used without any particular limitation as long as it has electrical conductivity. For example, carbon can be carbon black such as Ketjen black, acetylene black, channel black, fullerene, carbon nanotube, carbon nanofiber, amorphous carbon, carbon fiber, natural graphite, artificial graphite, graphitized Ketjen black, mesoporous carbon, vapor grown carbon fiber, etc. Carbon nanotubes can be single-walled carbon nanotubes (SWCNT) or multi-walled carbon nanotubes (MWCNT).
[0043] The carbon is preferably spherical carbon or carbon with an aspect ratio of 40 or less, and particularly preferably carbon with an aspect ratio of 10 or less. The aspect ratio is the ratio of the short side or diameter to the long side or length. When spherical carbon or carbon with this aspect ratio is compounded, the lithium vanadium oxide powder is easily crumbled in the process of forming the electrode material into an electrode. When the lithium vanadium oxide powder crumbles, the carbon that was incorporated inside the lithium vanadium oxide powder is exposed to the outside. Therefore, the carbon is distributed outside and inside the lithium vanadium oxide, and the conductivity of the electrode material is improved. As a result, a high charge amount is achieved even when the power storage device is charged at a high rate.
[0044] The content of spherical carbon or carbon with an aspect ratio of 40 or less is preferably 20 wt% or less in the composite. Even if the content is 20 wt% or less, spherical carbon or carbon with an aspect ratio of 40 or less exhibits a high charge amount during high-rate charging. By keeping the content at 20 wt% or less, a large amount of lithium vanadium oxide can be contained in the electrode material, resulting in a high-capacity electricity storage device.
[0045] As the spherical carbon, acetylene black or ketjen black is preferable. Acetylene black and ketjen black exhibit a higher charge amount for high-rate charging. In particular, ketjen black exhibits a higher charge amount for high-rate charging, even compared to the case where a composite is produced slowly over a long period of time using a process such as calcination and ball milling.
[0046] On the other hand, when using carbon nanotubes with an aspect ratio of 40 or more, the content should be 40 wt% or more of the composite. If the carbon nanotube content is 40 wt% or more, a higher charge amount can be achieved during high-rate charging, compared to when the composite is produced slowly over a long period of time using processes such as sintering and ball milling.
[0047] The composite may be manufactured by carrying out a first dispersion step using a homogenizer and a second dispersion step of subjecting the raw material liquid to UC treatment before the spray drying step. In the first dispersion step, coarse particles contained in the carbon, lithium source, and vanadium source in the composite are dispersed in a state in which the particle size is micronized by a homogenizer. In the second dispersion step, the composite containing the particles micronized in the first dispersion step is highly dispersed by using stress due to shear rise. By using the first and second dispersion steps in combination, each material in the composite is micronized, and a highly dispersed composite is obtained.
[0048] The homogenizer is composed of a drive unit, a fixed outer blade, and a rotating inner blade, and performs a series of homogenization processes including high-speed dispersion, fine grinding, and homogenization, thereby uniformly dispersing the vanadium source, lithium source, and carbon in the solvent.
[0049] The UC treatment is an ultra-centrifugal force processing method that induces a mechanochemical reaction. This UC treatment uses a reaction vessel equipped with an inner cylinder with a through hole inside the outer cylinder, and by rotating the inner cylinder, the vanadium source, lithium source, and carbon are collided with the inner wall of the outer cylinder by centrifugal force. The mechanical energy caused by this collision and the sliding up of the outer cylinder to the top of the inner wall highly disperses the carbon, especially, to the vanadium source and lithium source.
[0050] When doping a metal species M into a lithium vanadium oxide crystal to form a solid solution of Li3VO4 and Li4MO4, the material source of the metal species M can be dissolved in an aqueous solution together with the lithium source and the vanadium source. x V y M a O z As a material source of the metal species M, a compound containing the metal species M, an alkali metal, or an alkaline earth metal is used.
[0051] (Complex) According to this manufacturing method, the lithium vanadium oxide in the composite has a cation-disordered crystal structure. That is, in the X-ray diffraction incident angle 2θ, all or part of various long-range orders appearing in the range of angles lower than the peak around 32.2 degrees are broken and random. In other words, the order of the arrangement of the VO5 coordination structure and the LiO5 coordination structure at the distance appearing in the range of angles lower than the peak around 32.2 degrees is lost, or the proportion of the structure following the order is reduced.
[0052] FIG. 1 is a graph showing the results of analysis of lithium vanadium oxide crystals with respect to X-ray diffraction spectrum based on simulation and X-ray diffraction spectrum by powder X-ray diffraction measurement. FIG. 1(c) shows the X-ray diffraction spectrum by powder X-ray diffraction of a lithium vanadium oxide crystal having a β-phase crystal structure. FIG. 1(a) shows the X-ray diffraction spectrum of a lithium vanadium oxide crystal having a cation-disordered crystal structure obtained by powder X-ray diffraction. FIG. 1(b) shows the X-ray diffraction spectrum of a lithium vanadium oxide crystal having a long-range order obtained by powder X-ray diffraction measurement.
[0053] As shown in Figure 1 (a) to (c), a sharp peak appears when the incident angle 2θ is around 32.2 degrees. Note that "around 32.2 degrees" refers to 32.2±0.7 degrees. The sharp peak around 32.2 degrees indicates that the crystal structure of the lithium vanadium oxide crystal has an arrangement rule of LiO4 coordination structure and VO4 coordination structure with a periodic interplanar distance of 2.72 Å on the 020 plane.
[0054] As shown in Figure 1(c), the crystal structure of the β phase has five diffraction peaks in the range of angles lower than the diffraction peak near 32.2 degrees. Of the five diffraction peaks, one appears in the range of 25 to 30 degrees, three in the range of 20 to 25 degrees, and one in the range of 15 to 20 degrees. In order from the largest angle, the 111, 011, 101, 110, and 010 planes show the existence of an arrangement rule of the LiO4 coordination structure and the VO4 coordination structure with periodic interplanar distances of 3.17 Å, 3.66 Å, 3.90 Å, 4.13 Å, and 5.45 Å.
[0055] As shown in Figure 1(b), the crystal structure of lithium vanadium oxide crystals with long-range order has five diffraction peaks in the range of angles lower than the diffraction peak near 32.2 degrees as shown in Figure 1(c). Of the five diffraction peaks, one appears in the range of 25 to 30 degrees, three in the range of 20 to 25 degrees, and one in the range of 15 to 20 degrees.
[0056] The repeating pattern of the long-range arrangement of the LiO4 coordination structure and the VO4 coordination structure shown by these five diffraction peaks is called long-range order. In other words, lithium vanadate crystals having a β-phase crystal structure have five types of long-range order in the range of angles lower than the incidence angle 2θ of around 32.2 degrees. 5+ The coordination geometry of is tetrahedral.
[0057] On the other hand, as shown in (a) of Figure 1, when a cation-disordered crystal structure is adopted, all diffraction peaks present in the range of angles lower than the diffraction peak near 32.2 degrees have lower diffraction intensities than the diffraction peak near 32.2 degrees. Preferably, as shown in (a) of Figure 1, the diffraction peaks disappear in the range of angles lower than the peak near 32.2 degrees.
[0058] Since the composite contains lithium vanadium oxide crystals having a cation-disordered crystal structure and carbon, a step of mixing carbon to impart electrical conductivity is not required, which means that the risk of contact between the lithium vanadium oxide crystals having a cation-disordered crystal structure and moisture can be reduced. EXAMPLES
[0059] Hereinafter, examples of an electrode material in which lithium vanadium oxide and carbon are combined will be described in more detail, but the present invention is not limited to the following examples.
[0060] Example 1 An electrode material was produced by the manufacturing method of Example 1. The manufacturing method of Example 1 is shown in the flow chart of FIG. 2. As shown in FIG. 2, in the manufacturing method of Example 1, the lithium vanadium oxide material source and carbon were dissolved in an aqueous solution of pH 11.82 under indoor humidity, room temperature and atmospheric conditions, and then dried by a spray drying process. Between the preparation of the aqueous solution and the spray drying process, a stirring process of stirring with a homogenizer and a dispersion process of subjecting the raw material solution to UC treatment were interposed. After the spray drying process, the precipitate, which is the electrode material, was placed in a vacuum dryer and dried for 1 hour, and then moved to a glove box for storage.
[0061] In the preparation process, lithium hydroxide monohydrate represented by LiOH (Fujifilm Wako Pure Chemical Industries, Ltd.: 126-01211) was dissolved in ion-exchanged water (H2O). The LiOH aqueous solution was stirred for 5 minutes with a magnetic stirrer until it became colorless and transparent. Next, vanadium pentoxide represented by V2O5 (Kanto Chemical Co., Ltd.: 44017-00) was dissolved in the LiOH aqueous solution. The solution was stirred for 5 minutes with a magnetic stirrer until it became very light orange or colorless and transparent. Furthermore, Ketjen Black (Lion Specialty Chemicals Co., Ltd.: EC600JD) was dissolved as carbon in the LiOH aqueous solution, and the solution was stirred for 5 minutes with a magnetic stirrer until it became very light orange or colorless and transparent.
[0062] Lithium hydroxide was added at 1.2588g per 100mL of ion-exchanged water, and vanadium pentoxide was added at 0.9094g per 100mL of ion-exchanged water. This means that 30mmol of lithium hydroxide and 5mmol of vanadium pentoxide were dissolved in 100mL of ion-exchanged water. The aqueous solution contained lithium and vanadium in a ratio of 3:1 according to the stoichiometric ratio of Li3VO4. The pH of this aqueous solution was confirmed to be 11.82. In addition, 0.3394g of Ketjen Black was added per 100mL of ion-exchanged water. The aqueous solution contained 20wt% carbon based on the total weight of Li3VO4 and carbon.
[0063] In the first dispersion step using a homogenizer, dispersion was carried out for 30 minutes using a homogenizer (SONICS & MATERIALS Co., Ltd.: VCX500). In the second dispersion step using UC treatment, dispersion was carried out using a homogenizer with a force of 66,000 N (kgms -2 The inner cylinder was spun at a centrifugal force of 100 rpm for 5 minutes.
[0064] In the spray drying process, a spray dryer (BUCHI, Mini Spray Dryer B-290 (spray dryer)) was used to vaporize water from an aqueous solution of pH 11.82 in which vanadium pentoxide and lithium hydroxide were dissolved, at a vaporization rate of 1.67 ml / min or more. The inlet temperature was 160°C to 180°C, and the drying air velocity (aspirator flow velocity) was 38 m / s, the maximum value for the device. 3 / h, raw material supply flow rate (pump speed) 7.5 mL / min (instrument display: 25%), and nitrogen gas flow rate for spraying 473 L / h (instrument display: 40 mm).
[0065] (Examples 2 to 4) Furthermore, electrode materials were produced by the manufacturing methods of Examples 2 to 4. In the manufacturing method of Example 2, acetylene black (Denka Company, Ltd.: Denka Black) was added to the aqueous solution as carbon in the preparation step. 0.3394 g of acetylene black was added to 100 mL of ion-exchanged water so that the aqueous solution contained 20 wt % of carbon relative to the total weight of Li3VO4 and carbon. Other manufacturing steps and manufacturing conditions of Example 2 were the same as those of Example 1.
[0066] In the manufacturing method of Example 3, multi-walled carbon nanotubes (manufactured by UBE Corporation: AMC) were added to the aqueous solution as carbon in the preparation step. The aspect ratio of the multi-walled carbon nanotubes was 40 or more and 130 or less. 0.3394 g of multi-walled carbon nanotubes were added to 100 mL of ion-exchanged water so that the aqueous solution contained 20 wt % of carbon relative to the total weight of Li3VO4 and carbon. Other manufacturing steps and manufacturing conditions of Example 3 were the same as those of Example 1.
[0067] The manufacturing method of Example 4 was the same as that of Example 3, except that multi-walled carbon nanotubes were added to the aqueous solution as carbon in the preparation step. The aspect ratio of the multi-walled carbon nanotubes was 40 or more and 130 or less. Unlike Example 3, the aqueous solution was prepared so that it contained 40 wt% carbon with respect to the total weight of Li3VO4 and carbon. That is, 0.9051 g of multi-walled carbon nanotubes was added to 100 mL of ion-exchanged water. The other manufacturing steps and manufacturing conditions of Example 4 were the same as those of Example 1.
[0068] Comparative Example 1 Further, an electrode material was prepared by the manufacturing method of Comparative Example 1. In the manufacturing method of Comparative Example 1, a lithium vanadium oxide source other than carbon was added in the first preparation step. The lithium vanadium oxide source and the amount added were the same as those in Examples 1 to 4. After stirring the aqueous solution for 5 minutes with a magnetic stirrer until it became very light orange or colorless and transparent, the first dispersion step with a homogenizer and the second dispersion step with UC treatment were omitted and the process moved to a spray-drying step. The spray-drying step was carried out under the same conditions as those in Examples 1 to 4.
[0069] The precipitate obtained by the spray drying process was put into a planetary ball mill (Fritch Co., Ltd., PL-7). The ball mill container was made of zirconia with a volume of 20 mL, and zirconia balls with a diameter of 1 mm and a weight of 30 g were used. The same multi-walled carbon nanotubes as in Example 3 were further added to the planetary ball mill. The multi-walled carbon nanotubes were put into the planetary ball mill so that 20 wt% of carbon was contained relative to the total weight of Li3VO4 and carbon. The planetary ball mill was then operated at 300 rpm for 12 hours to composite the lithium vanadium oxide and the multi-walled carbon nanotubes.
[0070] An electrode for a power storage device was produced using a composite of lithium vanadium oxide and multi-walled carbon nanotubes. The composite was mixed with sodium carboxymethylcellulose and styrene butadiene rubber to form a slurry. The composite, sodium carboxymethylcellulose, and styrene butadiene rubber were mixed in a weight ratio of 95:2.5:2.5. This slurry was applied onto a copper foil current collector to form a layer of electrode material on the current collector, which was then vacuum dried at 80°C for 12 hours and rolled. The thickness of the electrode was 20 μm, and the layer density of the electrode material layer was 1.20 mg / cm. 2 It was.
[0071] (Observation of particle structure) The surface of the electrode material of Example 1 and the cross section of the electrode of Example 1 were observed with a scanning electron microscope. Figure 3 is an SEM image of the surface of the composite of lithium vanadium oxide and Ketjen black of Example 2, (a) at a magnification of 1,300 times, and (b) at a magnification of 10,000 times. Figure 4 is an SEM image of the cross section of the electrode using the composite of lithium vanadium oxide and Ketjen black of Example 1, (a) at a magnification of 2,200 times, and (b) at a magnification of 20,000 times.
[0072] As shown in Figure 3, it can be seen that Ketjen Black is composited on the surface of lithium vanadium oxide particles. Furthermore, as shown in Figure 3, many of the composites of lithium vanadium oxide and Ketjen Black are broken before being formed into an electrode, exposing the inside of the lithium vanadium oxide particles. Therefore, it can be seen that most of the Ketjen Black that was incorporated into the lithium vanadium oxide particles is exposed to the outside. As shown in Figure 4, Ketjen Black is exposed to the outside of the composite even after it is formed into an electrode.
[0073] In this way, a composite of lithium vanadium oxide and carbon is formed by adding a vanadium source, a lithium source, and carbon to water or a mixed solution containing water, adjusting the pH of the composite to 5 or more, spraying the composite and exposing it to hot air, and passing through a spray-drying process in which the liquid is evaporated from the composite, thereby forming a composite of lithium vanadium oxide and carbon. Moreover, since the crystallization of lithium vanadium oxide and the composite of carbon are achieved in a single spray-drying process, the manufacturing time of the electrode material is significantly shortened.
[0074] The surface of the electrode material of Example 2 and the cross section of the electrode of Example 2 were observed with a scanning electron microscope. Figure 5 is an SEM image of the surface of the composite of lithium vanadium oxide and acetylene black of Example 2, (a) at a magnification of 3,000 times, and (b) at a magnification of 9,000 times. Figure 6 is an SEM image of the cross section of the electrode using the composite of lithium vanadium oxide and acetylene black of Example 2, (a) at a magnification of 2,200 times, and (b) at a magnification of 20,000 times.
[0075] As shown in Figure 5, it can be seen that acetylene black is composited onto the surface of lithium vanadium oxide particles. In other words, it was confirmed that even if carbon black such as acetylene black, other than Ketjen black, is used as carbon, the crystallization of lithium vanadium oxide and the composite of carbon can be achieved in one step of the spray drying process.
[0076] As shown in Figure 6, even when acetylene black is used as carbon, it can be seen that the lithium vanadium oxide particles are crushed during the process of forming into an electrode, exposing the inside of the lithium vanadium oxide particles. Therefore, the second largest amount of carbon after acetylene black is exposed on the outside of the lithium vanadium oxide.
[0077] The surface of the electrode material of Example 3 and the cross section of the electrode of Example 3 were observed with a scanning electron microscope. Figure 7 shows SEM images of the composite of lithium vanadium oxide and 20 wt% multi-walled carbon nanotubes of Example 3, where (a) is a cross section at a magnification of 20,000 times, and (b) is a surface at a magnification of 20,000 times.
[0078] In addition, the surface of the electrode material of Example 4 and the cross section of the electrode of Example 4 were observed by a scanning electron microscope. Figure 8 shows SEM images of the surface of the composite of lithium vanadium oxide and 40 wt% multi-walled carbon nanotubes of Example 4, (a) at a magnification of 7,000 times, and (b) at a magnification of 30,000 times.
[0079] As shown in (a) of Figure 7, it can be seen that multi-walled carbon nanotubes are composited inside the lithium vanadium oxide particles. In other words, it was confirmed that even when fibrous carbon is used in addition to carbon black, the crystallization of lithium vanadium oxide and the composite of carbon can be achieved in one step of the spray drying process.
[0080] However, as shown in (b) of Figure 7, there were few multi-walled carbon nanotubes attached to the surface of lithium vanadium oxide particles. On the other hand, when the multi-walled carbon nanotubes were added at 40 wt% of the total of lithium vanadium oxide and carbon, it was confirmed that many multi-walled carbon nanotubes were also composited on the surface of the lithium vanadium oxide particles, as shown in (a) and (b) of Figure 8.
[0081] (Powder XRD) The electrode materials of Examples 1 to 4 were taken out of the glove box and analyzed by powder X-ray diffraction analysis at room temperature and humidity. In the powder X-ray diffraction analysis, a SmartLab from the equipment manufacturer Rigaku was used, and the range of 15°-40° was measured at 1.5° min -1The results are shown in Fig. 9. In Fig. 9, (a) shows the powder X-ray diffraction spectrum of Example 1, (b) shows the powder X-ray diffraction spectrum of Example 2, (c) shows the powder X-ray diffraction spectrum of Example 3, and (d) shows the powder X-ray diffraction spectrum of Example 4.
[0082] As shown in (a) to (d) of FIG. 9, the spectra of Examples 1 to 4 show a sharp peak at an incidence angle 2θ of about 32.2 degrees. This peak indicates that the canonical order of the LiO4 coordination structure and the VO4 coordination structure, which are cyclically spaced at 2.72 Å from the 020 plane, exists in the intermediate. Li3VO4 is composed of stacks of LiO4 tetrahedrons and VO4 tetrahedrons. The LiO4 tetrahedron is a tetrahedron in which four oxygen atoms share points with a lithium atom at the center, and the VO4 tetrahedron is a tetrahedron in which four oxygen atoms share points with a vanadium atom at the center. That is, it can be confirmed that the electrode materials of Examples 1 to 4 are composites of lithium vanadium oxide and carbon.
[0083] 9(a) to (d), in Examples 1 to 4, five peaks that should appear in the range of lower angles than the peak at an incident angle 2θ of about 32.2 degrees have disappeared. Specifically, the long-range order of the LiO4 coordination structure and the VO4 coordination structure with periodic interplanar distances of 3.17 Å, 3.66 Å, 3.90 Å, 4.13 Å, and 5.45 Å has disappeared on the 111, 011, 101, 110, and 010 planes. Therefore, it can be confirmed that the lithium vanadium oxides of Examples 1 to 4 have a cation-disordered crystal structure.
[0084] (Rate characteristics) The rate characteristics of the electrode materials of Examples 1 to 4 and Comparative Example 1 were evaluated. In evaluating the rate characteristics, the electrode materials of Examples 1 to 4 and Comparative Example 1 were molded into electrodes, and then the electrodes were used to prepare half cells of a lithium secondary battery. The half cells were 2032-type coin cells.
[0085] The molded electrode was the working electrode WE, and was punched out to a diameter of 14 mm. The counter electrode was a lithium metal with a diameter of 16.5 mm, which was attached to the bottom cover of a 2032-type coin cell. A polypropylene separator (Celgard 2400), the working electrode WE, and the top cover were placed on top of the counter electrode CE, in that order, and then crimped to create a cell. The electrolyte solvent was a mixture of ethylene carbonate (EC) and dimethyl carbonate (DEC) in a 1:1 volume ratio, and the solute was 1.0 M lithium hexafluorophosphate (LiPF6, manufactured by Kishida Chemical Co., Ltd.).
[0086] The potential range of the working electrode WE (V vs Li / Li+) was 0.1-2.5 V. During the output test, the lithium ion desorption was performed at 0.1 Ag per weight of lithium vanadate. -1 The current for lithium ion insertion was fixed at 10Ag. -1 It has even changed the
[0087] Fig. 10 is a graph showing the relationship between current density and capacity during discharge in Examples 1 to 3 and Comparative Example 1. Fig. 11 is a graph showing the capacity retention rate when discharged at each current density in Examples 1 to 3 and Comparative Example 1. In Fig. 11, -1 10 and 11, the plots of open circles indicate Example 1, the plots of open diamonds indicate Example 2, the plots of filled diamonds indicate Example 3, and the plots of filled circles indicate Comparative Example 1.
[0088] 10 and 11, in Examples 1 to 3, a vanadium source, a lithium source, and carbon are added to water or a mixed solution containing water to prepare a raw material solution of the composite, the raw material solution is adjusted to pH 5 or more, the raw material solution is sprayed and exposed to hot air, and the raw material solution is produced through a spray drying process in which the liquid is vaporized from the raw material solution. This production method also produces a composite of lithium vanadium oxide and carbon, and because the composite is cation-disordered, a good capacity is output even when discharged at a high rate.
[0089] Moreover, when spherical carbon black was used, the lithium vanadium oxide crystals were broken, exposing the carbon inside to the outside. Therefore, as shown in Figures 10 and 11, the discharge capacity and capacity retention rate were comparable to those of an electrode material manufactured by separately crystallizing lithium vanadium oxide and compositing it with carbon. In particular, when Ketjen black was used, the lithium vanadium oxide crystals were broken during the manufacturing process of the electrode material, exposing the carbon inside to the outside. Therefore, the capacity retention rate at high rates when Ketjen black was used surpasses that of an electrode material manufactured by separately crystallizing lithium vanadium oxide and compositing it with carbon.
[0090] Next, Fig. 12 is a graph showing the relationship between current density and capacity during discharge in Examples 3 and 4 and Comparative Example 1. Also, Fig. 13 is a graph showing the capacity retention rate when discharged at each current density in Examples 3 and 4 and Comparative Example 1. In Fig. 13, -1 12 and 13, the plots of filled circles indicate Example 3, the plots of open circles indicate Example 4, and the plots of filled diamonds indicate Comparative Example 1.
[0091] As shown in Figure 12, even when multi-walled carbon nanotubes are used, by adding 40 wt% or more of carbon to the composite, a discharge capacity comparable to that of an electrode material manufactured by separately combining lithium vanadium oxide crystallization and carbon can be obtained. Furthermore, as shown in Figure 13, it was confirmed that when 40 wt% or more of multi-walled carbon nanotubes are added to the composite, the capacity retention rate exceeds that of an electrode material manufactured by separately combining lithium vanadium oxide crystallization and carbon.
Claims
1. A method for producing an electrode material that is a composite of lithium vanadium oxide and carbon, comprising the steps of: providing water or a mixture containing water; a preparation step of preparing a raw material solution of the composite by adding a vanadium source, a lithium source, and the carbon to water or a mixed solution containing water; A pH adjustment step of adjusting the raw material liquid to a pH of 5 or more; a spray drying step of spraying the raw material liquid and exposing it to hot air to vaporize the liquid from the raw material liquid; containing, A method for producing an electrode material, comprising the steps of:
2. In the spray drying step, the lithium vanadium oxide is crystallized, the lithium vanadium oxide is changed to a cation disordered structure, and the lithium vanadium oxide is composited with the carbon. The method for producing the electrode material according to claim 1,
3. a dispersion step of dispersing the vanadium source, the lithium source, and the carbon prior to the spray drying step; The method for producing the electrode material according to claim 1,
4. a first dispersion step of dispersing the raw material liquid by a homogenizer before the spray drying step; a second dispersion step of introducing the raw material liquid into a reaction vessel and dispersing the vanadium source, the lithium source, and the carbon in the reaction vessel that is being rotated prior to the spray drying step; containing, The method for producing the electrode material according to claim 1,
5. In the preparation step, the carbon having a spherical shape or an aspect ratio of 40 or less is added; The method for producing the electrode material according to claim 1,
6. In the preparation step, carbon black is added as the carbon; The method for producing the electrode material according to claim 4,
7. In the preparation step, Ketjen black is added as the carbon; The method for producing an electrode material according to claim 5,
8. In the preparation step, the carbon is added to the composite in an amount of 20 wt % or less; The method for producing an electrode material according to claim 6 or 7, characterized by:
9. In the preparation step, carbon nanotubes are added as the carbon to the composite in an amount of 40 wt % or more; The method for producing the electrode material according to claim 1,
Citation Information
Patent Citations
Lithium vanadium oxide crystal, electrode material and energy storage device
JP7208147B2